Visual Effects Analysis in Building Messages Through Sequence in Anti-Hero Music Video - Sanjaya, William (Universitas Ciputra, 2025)
Visual effects are image manipulation and the creation of illusions from shooting that lead the audience to see the illusion of reality in the scenes. Visual effects can dramatize scenes so that messages can be conveyed to the audience. Thus, visual effects that are created in the right context could enhance the overall story.